2016
DOI: 10.17265/1934-7375/2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Caffeine and Ciprofloxacin onto Pyrolitically Derived Water Hyacinth Biochar: Isothermal, Kinetic and Thermodynamic Studies

Abstract: Abstract:In this work, the adsorptive features of water hyacinth (Eichhornia crassipes) derived biochar for sequestration of ciprofloxacin and caffeine from aqueous solution is reported. The isothermal behaviour, adsorption kinetics, mechanisms and thermodynamic parameters were investigated in batch mode. Langmuir and Freundlich models described the equilibrium adsorption data with regression values > 0.9. The kineticsdata obeyed the pseudo-second-order kinetic law while intraparticle pore diffusion was not th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 17 publications
0
0
1
Order By: Relevance
“…Contrary to the results of this research, the kinetic adsorption of caffeine onto biochar obtained from Eichhornia crassipes showed that the experimental data fitted well with the pseudo-second-order model [51]. Also, this model was the best for the kinetic adsorption of CFN onto activated carbon fibers (ACFs) from pineapple plant leaves [11], and in the kinetic adsorption of CFN onto char from the gasification of coal and pine activated with K2CO3 [52].…”
Section: Adsorption Isothermcontrasting
confidence: 93%
“…Contrary to the results of this research, the kinetic adsorption of caffeine onto biochar obtained from Eichhornia crassipes showed that the experimental data fitted well with the pseudo-second-order model [51]. Also, this model was the best for the kinetic adsorption of CFN onto activated carbon fibers (ACFs) from pineapple plant leaves [11], and in the kinetic adsorption of CFN onto char from the gasification of coal and pine activated with K2CO3 [52].…”
Section: Adsorption Isothermcontrasting
confidence: 93%